Cₙ² Modeling for Free-Space Optical Communications: A Review - Florian Quatresooz; Claude Oestges (IEEE Access)
Atmospheric turbulence influence on optical wave propagation, referred to as optical turbulence, has long been studied for astronomical applications and is now being addressed for free-space optical communication links between ground and satellites. While challenges overlap, models developed for astronomical applications are not fully transferable to optical communications. This paper provides a literature review of optical turbulence models, i.e., models giving vertical profiles of the refractive index structure parameter $C_{n}^{2}$ , highlighting differences between astronomical and optical communication sites. It presents different classifications of available $C_{n}^{2}$ models, based on the atmospheric layer they target and their necessary input parameters. Boundary layer $C_{n}^{2}$ models are also addressed, and recent machine learning approaches for $C_{n}^{2}$ modeling are discussed. Additionally, commonly used metrics for comparing $C_{n}^{2}$ profiles are introduced. Therefore, this work provides important insights into optical turbulence model selection, enabling accurate site characterization and informed optical terminal design.